2015
DOI: 10.1128/jvi.03713-14
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma-Associated Herpesvirus Latency-Associated Nuclear Antigen Inhibits Major Histocompatibility Complex Class II Expression by Disrupting Enhanceosome Assembly through Binding with the Regulatory Factor X Complex

Abstract: Major histocompatibility complex class II (MHC-II Kaposi's sarcoma-associated herpesvirus (KSHV) is an oncogenic gammaherpesvirus that causes several malignancies, such as Kaposi's sarcoma (KS), primary effusion lymphomas (PELs), and multicentric Castleman's disease (MCD), in immunocompromised individuals (1, 2). The life cycle of KSHV consists of a predominant latent phase marked by restricted gene expression and a transient lytic replication phase characterized by the production of functional virions. KSHV m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 79 publications
1
30
0
Order By: Relevance
“…6B, lower right). This difference may be due to the fact that HLA-DR␣ is regulated not only by RTA but also by the KSHV antigen LANA, a latency-associated protein which can transcriptionally inhibit MHC-II molecules, including HLA-DR␣ (42,45). Similar to previous studies, in this study we showed that exogenously expressed LANA can inhibit the MHC-II molecules, including HLA-DR␣ in BJAB cells (Fig.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…6B, lower right). This difference may be due to the fact that HLA-DR␣ is regulated not only by RTA but also by the KSHV antigen LANA, a latency-associated protein which can transcriptionally inhibit MHC-II molecules, including HLA-DR␣ (42,45). Similar to previous studies, in this study we showed that exogenously expressed LANA can inhibit the MHC-II molecules, including HLA-DR␣ in BJAB cells (Fig.…”
Section: Resultssupporting
confidence: 77%
“…Regulation of MHC-II molecules during the KSHV latent cycle by LANA has been well reported (42,45). However, how KSHV regulates MHC-II molecules during KSHV de novo infection remains largely unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The processed forms of LANA resulting from caspase cleavage blunt apoptosis and caspase 1-mediated inflammasome in KSHV-infected cells exposed to oxidative stress (24). LANA is also involved in the modulation of adaptive immunity by inhibiting antigen presentation of both major histocompatibility complex class I (MHC I) and class II (MHC II) (25)(26)(27)(28). Meanwhile, host restriction factors inhibit KSHV infection by activating immune responses.…”
mentioning
confidence: 99%
“…Approximately 2 × 10 6 293T cells were grown overnight per well in a 6 well plate. The target cells were transiently transfected with specific plasmids using Metafectene (Biontex Laboratories) as described previously [99]. Twenty-four hours post-transfection, the medium was changed and incubated with fresh medium.…”
Section: Luciferase Reporter Assaymentioning
confidence: 99%